The philosophical foundations of the modern competence linguodidactic paradigm - Кушнір, І. М. (Teaching Languages at Higher Educational Establishments at the Present Stage. Intersubject Relations, 2019)
The article focuses on the necessity of updating the model of a modern linguodidactic paradigm based on the newest philosophy of education which is the theoretical basis of the methodology of teaching Ukrainian as a foreign language. The relevance of the proposed article is due to the focus of the national strategy for the development of education in Ukraine, in particular, the education of foreign students, which is one of the important factors for the formation of the Ukrainian state as an equal partner in creating the global educational space. Modern trends of post-non-classical educational philosophy have been described by the author, such as a renewed vision of the content and results of education, updated with new requirements of a real changing globalized society. The creation of a global general educational, the introduction of a credit transfer system of training requires standardization of educational results. The formed set of competences of the future specialist, caused the need for the personality to be prepared for life in the modern unstable world and producing the competence-based nature of the modern educational paradigm, have been recognized as such a result. The reference point on the formation of competence is the basis for the most complete expression of the installation on the design of education as a social activity, leading to the development of the individuality of a person in the world that is constantly changing. Approaches to the definition of the phenomenon of competence have been analyzed in the article. The mastering of the target language takes place in the process of language education, the result of which develops a communicative competence, which has taken the leading place in the set of competencies of a university graduate at the present stage. The classic definition of a communicative competence also needs to be updated by the way of basing on the latest philosophical researches. The author makes a conclusion about such characteristic features of the modern competence paradigm of education: communicative rationality of the content of the educational process; the pluralism of ways of comprehending knowledge and ways of familiarizing oneself with a culture as an extensive open model of the world that is constantly changing; orientation of the educational process on the result as a set of qualities of the established personality, containing constant and variable components.